THE PATH FROM DISTRUST TO DEVIANCE: EXPLORING TURNOVER INTENTIONS AS A MEDIATOR BETWEEN PSYCHOLOGICAL CONTRACT VIOLATION AND WORKPLACE MISCONDUCT - Mwangi, Esther Wanjiku; Otieno, Paul Onyango (Research Journal of Economics and Sustainable Development, 2024)
This study analyzed the mediating effect of turnover intention (TI) on the relationship between psychological contract violation (PCV) and workplace deviance (WPD), the effects of PCV on TI, and TI on WPD. Explanatory research design was used employing stratified random sampling techniques to collect data from 443 employees of Agriculture and Food Authority Directorates in Kenya. Self-administered structured questionnaires anchored on 7-point Likert scale were used to collect data. Reliability and validity of the research instrument were tested using Cronbach Alpha and Factor Analysis respectively. Regression based Hayes Process Macro model 4 was used to test the mediation effect. The results of the study showed a negative but significant mediation effect of TI on the relationship between PCV and WPD. In addition, the study established that PCV has an influence on TI, and TI also influences WPD. The findings of the study accentuate the need for the human resource managers in public organizations to delve into the problem of turnover intention and come up with appropriate mitigation strategies, so as to reduce the drawback of workplace deviance. This study contributes to the theoretical knowledge base of WPD by including TI as a mediator. It also adds into the literature of psychological contract and the social exchange theories.